Perspective on computer ethics and security : understanding university students - Masrom, Maslin (Penerbit UTM, 2008)
In our modern life, ethics has become an increasingly important issue. Many computer users are not aware of the ethics in using computer. Students are often perceived to have little understanding of the ethical issues associated with the use of computers, such as privacy, property, accuracy, accessibility and social impact. Computer ethics is one of the issues that comes with computer technology. It can be defined as a category of professional ethics similar to medical, legal, teaching and accounting ethics. According to Langford (1995) ethics encourage individuals to think through their attitudes and beliefs and thus be able to decide in advance whether their opinions are appropriate or not, and once this is decided, individuals should then be prepared to accept full responsibility for their actions. Computer security refers to the protection of data (information security), networks and computing power. Malaysian government has shown its commitment in the use of information and communication technology for national development and is moving towards a knowledge-based society. This is witnessed through the huge national budget allocation for information and communication technology development. Nevertheless, the negative impact of technology cannot be denied. Understanding computer ethics in security element is an important feature. This provides an avenue to further understand the issues related to computer ethics and security. Few Malaysian universities offer selective course related to computer ethics and security. The student population therefore is rather unfamiliar and uncertain with the idea that ethical and security matters might be of importance to them in their future career. Given that today’s undergraduate students are the employees of tomorrow and if the ethics they have as undergraduates shape their behaviours in the future, then we need to understand and address this gap in students’ ethical behaviours before they enter the working arena. Further, even though the literature contains a variety of research on ethics and information and communication technology, there has been a lack of empirical research on studying student perceptions’ of ethical issues in using information and communication technology, particularly in Malaysia. This chapter describes the undergraduate students’ perceptions of computer ethics and security within the academic setting. The rest of the chapter is organised as follows. Section 2 discusses the background. In Section 3, the undergraduate students’ perceptions are described and discussed, and Section 4 presents the conclusions.